Pelos olhos das crianças: uma etnografia da favela do Gonzaga - Begnami, Patricia dos Santos (2008)
This research had the objective to enlarge and to deepen the suburb analysis, using as an object the Gonzaga shantytown, located in São Carlos, in the countryside of the state of São Paulo, and a neighborhood spotted by the population of the city as a troubled one, and the home of most of the criminals operating in the city, since it s one of the neighborhoods where most inhabitants have low incomes. Through the ethnography focused on the study of a case, the Gonzaga shantytown, I have revised the co-extensive relation between two generation universes: the adult and the infantile, investigating the sociability in the neighborhood, using as objects, the street, the relationships among the children, and also the relationships between the children, their parents and their relatives. In sum, I have investigated through the field research, the participating observation, the ethnography as the children are committed with the configuration, and the net of social activities in the neighborhood and how all that is represented and portrayed in the children s behavior and sociability, as much as in their ludic activities. In this research, the main role is played by the children, therfore the text was built from the children s point of view; they are interlocutors. Thus, the children were treated as subjects, capable of representing and signifying their own experiences, as actors and social agents that signify, and not merely re-signify their social environment, and that perceive the world and represent it in their own way. At last, this research shows how the Gonzaga shantytown s children represent and signify the neighborhood where they live in, and, because of the children, we are able to know the life experience of those who live in the suburbs or in shantytowns, which is different than the one presented by the tv channels and the newspapers, medias that do not realize the diversity of inhabitants in these neighborhoods.